Inclusion properties of hydroxy host compounds - Bourne, Susan Ann (Department of Chemistry, 2016)
Inclusion compounds can be defined as those in which one type of molecule is able to enclose another molecule (usually smaller) within its structure, leaving the bonding systems of both components unchanged. The molecular network and the enclosed species are usually referred to as the "host" and "guest" respectively. The ability of four hydroxyl-containing molecules to form inclusion compounds was studied. Each of these molecules has a tetrahedral carbon or silicon atom bonded to an hydroxyl group and shielded by two or three aromatic moieties. The bulkiness of these molecules prevents them from crystallizing in a close-packed fashion while the hydroxyl groups enable them to participate in hydrogen bonding. The formation and characterisation by single crystal X-ray diffraction methods of two non-porous α-phase compounds and eighteen inclusion compounds have been described. The inclusion compounds were divided into four classes : Class A consisted of compounds of 1, 1,2,2-tetraphenylethane-1,2-diol, Class B consisted of compounds of triphenylmethanol, Class C consisted of compounds of triphenylsilanol and Class D consisted of compounds of tri-1-naphthylsilanol. A number of guest compounds were chosen. Most had at least one atom which could act as an acceptor in a hydrogen bond. Hydrogen bonding (host-host, host-guest or a combination of these) proved to be the greatest stabilizing force in these compounds. The shape and size of the cavities available for guests were analysed by means of volume calculations. The thermal decomposition of the inclusion compounds was studied by Thermogravimetry (TG) and Differential Scanning Calorimetry (DSC), to determine the forces holding the guest within the structure and the changes in the host lattice as the guest was desorbed. X-ray powder diffraction methods were also used to confirm phase changes that occurred with guest loss. In addition, Thermogravimetry was used to determine the activation energy of the guest desorption process. 1, 1,2,2-Tetraphenylethane-1,2-diol was shown to include 3,5-lutidine preferentially from mixtures of 2,6- and 3,5-lutidine, provided that the mole fraction of 3,5-lutidine exceeded 0.30. Triphenylsilanol was selective to ethanol from equimolar mixtures of ethanol and other simple alcohols. Ethanolic solutions of up to 40%(w /w) water also yielded only the 4: 1 triphenylsilanol•ethanol complex. Host-guest interactions were quantified using the method of atom-pair potentials. The position of the guest molecule was varied to allow a minimum potential energy to be calculated. Comparison across a series of related inclusion compounds showed a qualitative correlation between the enthalpy of guest release, ΔH (measured by DSC), and the minimum potential energy of the guest within the crystal structure.